Self-regulated learning strategies and academic performance of accounting students at a South African university - Papageorgiou, E. (South African Journal of Higher Education, 2022)
Orientation: Knowledge of a subject and cognitive strategies are usually not enough to increase students’ academic performance; students need also to be motivated to use learning strategies and deal with test and examination anxiety to be successful, especially in their first year of study. Purpose: The purpose of the study was to measure first-year accounting students’ motivational aspects and learning strategies versus academic performance at a South African university. Research questions: Three research questions were used to determine if students were motivated and applied learning strategies to perform in the accounting course: 1) What motivational variables and learning strategies are related to academic performance measuring students’ final Accounting marks, controlling for admission requirements, gender, race, and degree choice? 2) Are prior knowledge demographic and degree choice related to motivational variables and learning strategies? 3) Are motivational variables related to learning strategy variables for Accounting students regarding their Degree choice? Method: A full scale “Motivated Strategies for Learning Questionnaire” (MSLQ) was used to assess accounting students’ (N=617) motivational orientations and their use of different learning strategies for an accounting course. Multiple regression analysis was applied to explore the relationship among the different variables. Findings: The findings of this study are relevant to learning in predicting academic performance of first-year accounting students and relationships between self-regulated learning and students’ degree choice, gender, race, academic performance and admission requirements. Limitation and further recommendation: This study was only deployed to accounting students at one South African university. A further recommendation would be to collaborate with other disciplines and universities to determine if motivational and learning strategies differ from those of accounting students at a South African university. Value of the study and practical implications: The value of the study provides insights and evidence on motivational beliefs and learning strategies of students in accounting studies and how students can improve their academic performance.